AN ANALYSIS OF DIFFICULTIES FACED BY STUDENTS IN LEARNING READING AT SMA NEGERI 1 BAUBAU - Nety, Nety; Wahyuni B, Asti; Husen, Hartina (English Education Department, 2023)
The problem of this research was what were the difficulties faced by students at SMA Negeri 1 Baubau especially in eleventh grade students in learning reading comprehension? The objective of this research was to find out the difficulties faced by the eleventh grade students at SMA Negeri1 Baubau in learning reading comprehension. The researcher used the descriptive qualitative research. In this research descriptive was conducted in the purpose to describe systematically about the fact and characteristic of the difficulties that students faced in learning reading. The subject of the research was class XI MIPA 4 SMA Negeri 1 Baubau with the total subject consisted of 40 students then the sample of the research consist of 10 student. The instrument of this research used observation and interview, while the technique of data analysis used the of Miles and Huberman adapted that consist of data reducing, data display and drawing conclusion/verification. The result of research indicated that there were difficulties faced by the eleventh grade students at SMA Negeri 1 Baubau in learning reading comprehension. Regarding in the analysis of this research, there were four findings in this research, namely: Difficulty to understand the meaning of the word: Not understand the main idea, not understand the grammar, and difficulties to make inferences.